Attributes and drivers of audit quality : the perceptions of quality inspectors in the UK - Noor Adwa Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examines the UK’s Audit Quality Review’s quality inspectors’ perceptions of attributes and drivers of audit quality. A survey questionnaire was distributed to quality inspectors with high ‘performance of the audit process’ and low ‘client service quality’ as relevant attributes for audit quality. A range of internal factors – behavioural, technical and relational – is perceived to affect audit engagements and potentially cause variation in audit quality between audits. Further, competition in the audit market and audit regulation are perceived as key contextual factors in the auditing environment affecting audit quality. Half of the quality inspectors perceived the level of audit quality in practice varies in different audit engagements. The majority highlighted the lack of challenge by the external auditors and adequacy of evidence and documentation as two key recurring issues in the inspection process. This study extends the scope of prior research by gathering perceptions of quality inspectors on a broader spectrum of attributes and drivers on audit quality that have not been previously studied in this line of research. The findings have implications for regulators and audit practitioners in monitoring and promoting audit quality in practice.